A Morphometric and Multivariate Analysis Approach to Prioritization of Sub-Watershed: A case study on Muzaffarpur District of Bihar, India - Saket Raj; Kishan Singh Rawat (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The goal of the present study, which was undertaken as a research, was to Prioritization of Sub-Watershed using Morphometric and Multivariate Analysis.